2017
DOI: 10.4103/jehp.jehp_34_16
|View full text |Cite
|
Sign up to set email alerts
|

Empowerment in breastfeeding as viewed by women: A qualitative study

Abstract: BACKGROUND:The positive effect of breastfeeding on health is globally accepted. However, breastfeeding has not yet practiced at a favorite level. Empowerment of mothers is an important factor for continuing breastfeeding. This study was conducted to explore women's perception of empowerment in breastfeeding.METHODS:The present qualitative study was conducted in conventional content analysis method. Thirty-four semi-structured deep interviews were conducted with 18 mothers, four key family members, and 12 other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
(25 reference statements)
1
7
0
Order By: Relevance
“…The findings of the present study indicate that adequate knowledge and skills for breastfeeding practices have a positive effect on the formation of breastfeeding empowerment. This result was similar to a study by Heidari, Kohan and Keshvari (2017) which also showed that the participants' knowledge and skills to prevent and solve breastfeeding problems, and self-efficacy in solving breastfeeding problems are some of the significant factors of empowerment in breastfeeding. A study by Kang, Choi and Ryu (2008) showed that the breastfeeding empowerment was effective in increasing the breastfeeding rate and helped mothers to actively solve problems and cope with difficulties.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings of the present study indicate that adequate knowledge and skills for breastfeeding practices have a positive effect on the formation of breastfeeding empowerment. This result was similar to a study by Heidari, Kohan and Keshvari (2017) which also showed that the participants' knowledge and skills to prevent and solve breastfeeding problems, and self-efficacy in solving breastfeeding problems are some of the significant factors of empowerment in breastfeeding. A study by Kang, Choi and Ryu (2008) showed that the breastfeeding empowerment was effective in increasing the breastfeeding rate and helped mothers to actively solve problems and cope with difficulties.…”
Section: Discussionsupporting
confidence: 89%
“…Two systematic reviews of research mostly from developing countries have demonstrated the influence of grandmothers (Aubel 2012;Negin et al 2016). Other studies also mentioned that receiving breastfeeding support from the health care provider, family and society is an important source of emotional support during the postpartum period (Heidari, Kohan and Keshvari 2017;Nelson 2006;Di Manno, Macdonald and Knight 2015). Previous findings have also established the importance of the nurse as a source of breastfeeding information and support (Isabella and Isabella 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing awareness of the modifiable barriers experienced by mothers during breastfeeding may help health professionals in the detection of mothers at risk for early cessation of breastfeeding and the implementation of targeted breastfeeding support [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Interventions focusing on assisting a lactating parent with identifying their own power through breastfeeding/chestfeeding education and skills may help to increase breastfeeding/chestfeeding duration and initiation (Heidari et al, 2017).…”
Section: Discussionmentioning
confidence: 99%